How baseball spin influences the performance of a pitcher - Tomoyuki Nagami; Takatoshi Higuchi; Kazuyuki Kanosue (Japanese Society of Physical Fitness and Sports Medicine, 2013)
In the present review, we include a series of recent experiments in order to update and summarize the characteristics of ball spin in baseball pitching. The motion of a ball thrown by a pitcher is influenced by three forces: gravity, the drag force due to air resistance, and the lift force which deflects a ball vertically or laterally due to the Magnus effect (Magnus force). The forces acting on a baseball are influenced by the ball's translational speed and spin rate as well as the orientation of the spin axis. The lift force acting on the ball becomes greater with increases in the "spin parameter" (proportion of the spin rate and the movement speed) when the spin axis of the ball is orthogonal to the direction of movement. On the other hand, when the spin axis is located in line with the direction of the movement (so-called "gyro ball"), the drag force becomes smaller and the lift force decreases to nearly zero regardless of the spin parameter. The orientation of the spin axis also affects the direction of the lift force on the ball; that is, the lift force acts perpendicular to the cross product of the spin axis and the direction of motion. There are great variations in the spin of fastballs; both spin rate and orientation of the spin axis vary widely across individual pitchers. When the spin rate is extremely low, such as with a knuckle ball, the amount and direction of lift force changes irregularly during flight. This is caused by seams on the ball surface, which cause an unpredictable "fluttering" trajectory. The reason for the success of pitchers that can produce abnormal or unique ball spins is discussed.